Object-Database Approach for a Hypervideo Platform - A. Memon, Qurban; A. Khoja, Shakeel (Malaysian Journal of Computer Science, 2003)
Web users are seizing on interactive capabilities that software suppliers have developed, and are eagerly awaiting new interactive capabilities now being demonstrated. The capabilities currently being explored include video browsing. This paper focuses on the development of a rich information environment based on a customized platform that enables hyperlinks on objects within a digital video. With the help of such an environment, the user is able to view multiple videos concurrently and browse them spatially and temporally, with the help of an object database. Specifically, the platform is expected to enable users to traverse through that object by linking, and such links have been explored. The links may connect to within a video, or multiple running videos and/or World Wide Web object. The issues such as open hypermedia link base and object database versus multiple videos are also investigated.